Millennial-scale carbon accumulation and dynamics in mangroves: A case study from the Upper Gulf of Thailand - Ausanee Suttiwong; Paramita Punwong; Rob Marchant; Apichaya Englong; Luke Andrews; Nathsuda Pumijumnong; Wanwisa Pansak; Pasin Maprasop (Science of The Total Environment, 2026)

Long-term vegetation dynamics, environmental changes, anthropogenic records, and carbon accumulation during 3,800 years in Krabi mangroves, Thailand - Apichaya Englong; Paramita Punwong; Rob Marchant; Akkaneewut Jirapinyakul; Sasivimon C. Swangpol; Ponlachart Chotikarn; Nathsuda Pumijumnong; Prae Chirawatkul; Pasin Maprasop; Phatra Samerwong; Ausanee Suttiwong (Vegetation History and Archaeobotany, 2026)

Unprecedented Burning in Tropical Peatlands During the 20th Century Compared to the Previous Two Millennia - Yuwan Wang; Ted R. Feldpausch; Graeme T. Swindles; Patrick Moss; Hamish A. McGowan; Thomas G. Sim; Paul J. Morris; Adam Benfield; Colin Courtney‐Mustaphi; David Wahl; Encarni Montoya; Esther Githumbi; et al. (Global Change Biology, 2026)
Tropical peatland wildfire incidence has risen in recent decades, driven by drainage for land use and intensified by severe droughts with global climate change. These disturbances have altered vegetation structure, disrupted ecosystem functioning, and increased carbon emissions, particularly in Southeast Asia. However, the long‐term history and characteristics of wildfires in tropical peatlands remain largely unknown. Here, we compiled fifty‐eight macro‐charcoal records from peatlands across the tropics, ranging from lowland forested to montane peatlands, to assess millennia‐scale changes and controlling factors of tropical peatland burning. We divided the datasets into four main sub‐regions: Neotropical, Afrotropical, Indomalayan and Australasian ecoregions to explore regional variability. Tropical peatlands had high burning levels between 0 and 850 ce , followed by a relatively low and stable period until a marked increase during the 20th century. The general trend in tropical peatland burning follows changes in global temperature, and climate variables that control the length and severity of drought events have a notable influence on peat burning before 1900 ce . During the 20th century, regional differences were observed, with declining fire trends in the Neotropical and Afrotropical regions and increasing fire trends in the Indomalayan and Australasian regions. This difference is likely attributable to human activities, and such intervention is also evident in palm swamps and hardwood swamps under similar wet, weakly seasonal climates. With the increase in anthropogenic pressures on peatlands and greater climate variability, future wildfires in peatlands are likely to become more frequent and widespread across all tropical ecoregions. Conservation and sustainable land‐use practices could be used to mitigate and control peatland burning and protect these carbon‐rich sinks.

Late Quaternary Montane Forest Dynamics From Equatorial East Africa: A Biome Perspective - Esther N. Githumbi; Jemma Finch; Rahab N. Kinyanjui; Colin Courtney‐Mustaphi; Paul Musili; Stephen Rucina; Julius Lejju; Peter Liljenberg; Rob Marchant (Journal of Biogeography, 2025)
Aim Understanding environmental change over large spatial and temporal scales requires working at a broad ecological scale to enable cross‐site comparisons. This allows data‐based comparisons to dynamic vegetation model outputs, with utility for climate and land cover modelling. We synthesise multisite pollen data at the biome level to understand Equatorial Afromontane ecosystem response to climate change over the last 50,000 years and quantitatively document the timing, character and spatial patterns of ecosystem transitions. Location Mountains of Equatorial East Africa. Time Period Late Quaternary (50,000 cal year BP–present). Taxon Angiosperms (trees, shrubs and grasses), gymnosperms (conifers), pteridophytes (ferns) and bryophytes (clubmosses). Methods A literature review revealed 58 available published pollen sites from Equatorial East African Mountains. Original geochronological and palynological data were collated from 34 sites from the African Pollen Database (APD) and directly from authors. Pollen taxonomies were updated and harmonised using the African Plant Database. The geochronologies were reanalysed and radiocarbon data ( n = 219) were IntCal20 calibrated to develop linearly interpolated age‐depth models. The 636 pollen taxa were grouped into 21 plant functional types and combined into seven biomes that represent the range of montane ecosystems. A rate of change analysis at each site provided a scale of the change through time at each site. Results Mesic montane forest biomes were present throughout the 50,000 cal year BP. Cold and dry montane biomes expanded during and after the Last Glacial Maximum (LGM). Warm and wet forest biomes expanded from the early Holocene and more open biomes expanded in the Late Holocene. Regional differences were observed, such as the Eastern Arc Mountain sites recording relatively little change in comparison with isolated volcanic mountains. The rate of change analysis highlights periods with a high rate of change (45,000–35,000, 11,000–5000 and 5000–present) while 35,000–20,000 is relatively stable. Main Conclusions Equatorial East African Montane forests are driven by local to regional vegetation responses to past climate changes. The research highlights that both the pace and nature of interactions in ecological systems vary widely across these montane forests.

Near and far future conservation, land use, and land cover interactions around the wider Etosha landscape, north-central Namibia - Rebecca W. Kariuki; Jessica P. R. Thorn; John K. E. Mfune; Rob Marchant; Claudia Capitani (Regional Environmental Change, 2025)

Multiporate Poaceae pollen grains observed in the recent fossil record from the Greater Serengeti Ecosystem and Lake Victoria region - Colin J. Courtney Mustaphi; Sandra O. Camara-Brugger; Anneli Ekblom; Linus Munishi; Rebecca Kariuki; Anna Shoemaker; Paul Lane; Rob Marchant (Review of Palaeobotany and Palynology, 2025)

Exploring the Interface Between Planetary Boundaries and Palaeoecology - Lindsey Gillson; Alistair Seddon; Ondřej Mottl; Ke Zhang; Kelly Kirsten; Peter Gell; Rob A. Marchant; Christoph Schwörer; Estelle Razanatsoa; Paul J. Lane; Colin J. Courtney‐Mustaphi; John Dearing (Global Change Biology, 2025)
The concepts of planetary boundaries are influential in the sustainability literature and assist in delineating the ‘safe operating spaces’ beyond which critical Earth system processes could collapse. Moving away from our current trajectory towards ‘hothouse Earth’ will require knowledge of how Earth systems have varied throughout the Holocene, and whether and how far we have deviated from past ranges of variability. Such information can inform decisions about where change could be resisted, accepted or where adaptation is inevitable. The need for information on long‐term (Holocene) change provides an interface for palaeoecology and sustainability that remains underexploited. In this position paper, we explore this interface, first discussing the need for long‐term perspectives and introducing examples where palaeoecology has been used in defining safe operating spaces and constraining limits of acceptable change. We describe advances in quantitative methods for analysis of time‐series data that strengthen the contribution of palaeoecology to the concepts of planetary boundaries and safe operating spaces. We consider the importance of issues of scaling from landscape to regional and global scales in operationalising planetary boundaries concepts. We distil principles for this field of research going forward and introduce three case studies which will form the basis of research on these topics.

Pathways from research to sustainable development: Insights from ten research projects in sustainability and resilience - Anna Scaini; Joseph Mulligan; Håkan Berg; Albert Brangarí; Vera Bukachi; Sebastian Carenzo; Da Chau Thi; Colin Courtney-Mustaphi; Anneli Ekblom; Hanne Fjelde; Mathias Fridahl; Anders Hansson; et al. (Ambio, 2024)
Drawing on collective experience from ten collaborative research projects focused on the Global South, we identify three major challenges that impede the translation of research on sustainability and resilience into better-informed choices by individuals and policy-makers that in turn can support transformation to a sustainable future. The three challenges comprise: (i) converting knowledge produced during research projects into successful knowledge application; (ii) scaling up knowledge in time when research projects are short-term and potential impacts are long-term; and (iii) scaling up knowledge across space, from local research sites to larger-scale or even global impact. Some potential pathways for funding agencies to overcome these challenges include providing targeted prolonged funding for dissemination and outreach, and facilitating collaboration and coordination across different sites, research teams, and partner organizations. By systematically documenting these challenges, we hope to pave the way for further innovations in the research cycle.

Late Pleistocene montane forest fire return interval estimates from Mount Kenya - Colin J. Courtney Mustaphi; Stephen M. Rucina; Rob Marchant (Journal of Quaternary Science, 2023)
Past forest fire events and fire frequencies are reconstructed with sediment–charcoal records at lake catchment spatial scales. Few quantitative palaeofire analyses exist in tropical montane forests, where fire return intervals are long (decadal and centennial scales) because of the infrequency of fire weather and fuel conditions. Fire return intervals are a key characteristic of fire regimes and changing fire frequencies rapidly alter land cover compositions and vegetation structure. Charcoal records from small lakes with relatively small catchments covered with dense forest provide an opportunity to reconstruct low‐frequency, high‐severity fires through a time series decomposition approach to identify charcoal peaks above a varying background rate as a proxy for palaeofire events. The sediment core from Rumuiku wetland on Mount Kenya, equatorial eastern Africa, accumulated a nearly linear age–depth model and provided a high temporal resolution (10 years cm –1 ) sieved charcoal count record (>125 µm). Pollen analysis showed a significant change in montane forest assemblage occurred at 21 200 cal a bp from a montane forest with abundant Podocarpus and Juniperus to a forest with more abundant Hagenia . This change in forest altered the vegetation composition and structure with concomitant changes to the fire regime. Forest biomass in the Hagenia forests decreased and it is likely that fire activity qualitatively changed toward lower intensity and lower severity fires. The quantitative fire event reconstruction focuses on the interval from 27 000 to 16 500 cal a bp and the older montane forest that experienced higher severity fires from 27 000 to 21 200 cal a bp, which reconstructed a temporally heterogeneous fire regime with fire return intervals that ranged from 30–430 years and a mean of 120 years (median 160 years) in the catchment. These are the first estimates of fire return intervals of mountain forests in eastern Africa. We then explore the potential for further comparative research and incremental research contributions to improve quantitative and qualitative palaeofire research in tropical forest ecosystems. We discuss the potential to use these types of data for characterizing variables of fire regimes prior to ostensibly significant modification by anthropogenic activity as well as during the recent past as human land use pressures increased within Afromontane forests.

Documenting a thousand years of environmental and anthropogenic changes on mangroves on the Bangkok coast, the upper Gulf of Thailand - Paramita Punwong; Sureeporn Promplin; Charinee Lomchantrasilp; Pornuma Soonthornampaipong; Apichaya Englong; Rob Marchant; Katherine Selby; Prae Chirawatkul (Vegetation History and Archaeobotany, 2023)

Climate change and hunter-gatherers in montane eastern DR Congo - Rodrigue Batumike; Franklin Bulonvu; Gérard Imani; Desiré Akonkwa; Aimable Gahigi; Julia A. Klein; Rob Marchant; Aida Cuni-Sanchez (Climate and Development, 2022)

Late Holocene environmental change and anthropogenic: Ecosystem interaction on the Laikipia Plateau, Kenya - Veronica Muiruri; Rob Marchant; Stephen M. Rucina; Louis Scott; Paul J. Lane (Ambio, 2022)
East African ecosystems have been shaped by long-term socio-ecological–environmental interactions. Although much previous work on human–environment interrelationships have emphasised the negative impacts of human interventions, a growing body of work shows that there have also often been strong beneficial connections between people and ecosystems, especially in savanna environments. However, limited information and understanding of past interactions between humans and ecosystems of periods longer than a century hampers effective management of contemporary environments. Here, we present a late Holocene study of pollen, fern spore, fungal spore, and charcoal analyses from radiocarbon-dated sediment sequences and assess this record against archaeological and historical data to describe socio-ecological changes on the Laikipia Plateau in Rift Valley Province, Kenya. The results suggest a landscape characterised by closed forests between 2268 years before present (cal year BP) and 1615 cal year BP when there was a significant change to a more open woodland/grassland mosaic that continues to prevail across the study area. Increased amounts of charcoal in the sediment are observed for this same period, becoming particularly common from around 900 cal year BP associated with fungal spores commonly linked to the presence of herbivores. It is likely these trends reflect changes in land use management as pastoral populations improved and extended pasture, using fire to eradicate disease-prone habitats. Implications for contemporary land use management are discussed in the light of these findings.

Late Pleistocene and Holocene Afromontane vegetation and headwater wetland dynamics within the Eastern Mau Forest, Kenya - Esther N. Githumbi; Colin J. Courtney Mustaphi; Rob Marchant (Journal of Quaternary Science, 2021)
The Mau Forest Complex is Kenya's largest fragment of Afromontane forest, providing critical ecosystem services, and has been subject to intense land use changes since colonial times. It forms the upper catchment of rivers that drain into major drainage networks, thus supporting the livelihoods of millions of Kenyans and providing important wildlife areas. We present the results of a sedimentological and palynological analysis of a Late Pleistocene–Holocene sediment record of Afromontane forest change from Nyabuiyabui wetland in the Eastern Mau Forest, a highland region that has received limited geological characterization and palaeoecological study. Sedimentology, pollen, charcoal, X‐ray fluorescence and radiocarbon data record environmental and ecosystem change over the last ~16 000 cal a bp. The pollen record suggests Afromontane forests characterized the end of the Late Pleistocene to the Holocene with dominant taxa changing from Apodytes , Celtis , Dracaena , Hagenia and Podocarpus to Cordia , Croton , Ficus , Juniperus and Olea . The Late Holocene is characterized by a more open Afromontane forest with increased grass and herbaceous cover. Continuous Poaceae, Cyperaceae and Juncaceae vegetation currently cover the wetland and the water level has been decreasing over the recent past. Intensive agroforestry since the 1920s has reduced Afromontane forest cover as introduced taxa have increased ( Pinus , Cupressus and Eucalyptus ).

Climate change and pastoralists: perceptions and adaptation in montane Kenya - Aida Cuni-Sanchez; Peter Omeny; Marion Pfeifer; Lydia Olaka; Mamo Boru Mamo; Rob Marchant; Neil D. Burgess (Climate and Development, 2019)

Late Holocene wetland transgression and 500 years of vegetation and fire variability in the semi-arid Amboseli landscape, southern Kenya - Esther N. Githumbi; Colin J. Courtney Mustaphi; Kevin J. Yun; Veronica Muiruri; Stephen M. Rucina; Rob Marchant (Ambio, 2018)

An 800 year record of mangrove dynamics and human activities in the upper Gulf of Thailand - Paramita Punwong; Sanpisa Sritrairat; Katherine Selby; Rob Marchant; Nathsuda Pumijumnong; Paweena Traiperm (Vegetation History and Archaeobotany, 2018)

Harvesting fodder trees in montane forests in Kenya: species, techniques used and impacts - Aida Cuni-Sanchez; Marion Pfeifer; Rob Marchant; Patrícia V. Pompeu; Neil D. Burgess (New Forests, 2018)

Land cover change and carbon emissions over 100 years in an A frican biodiversity hotspot - Simon Willcock; Oliver L. Phillips; Philip J. Platts; Ruth D. Swetnam; Andrew Balmford; Neil D. Burgess; Antje Ahrends; Julian Bayliss; Nike Doggart; Kathryn Doody; Eibleis Fanning; Jonathan M. H. Green; et al. (Global Change Biology, 2016)
Agricultural expansion has resulted in both land use and land cover change ( LULCC ) across the tropics. However, the spatial and temporal patterns of such change and their resulting impacts are poorly understood, particularly for the presatellite era. Here, we quantify the LULCC history across the 33.9 million ha watershed of Tanzania's Eastern Arc Mountains, using geo‐referenced and digitized historical land cover maps (dated 1908, 1923, 1949 and 2000). Our time series from this biodiversity hotspot shows that forest and savanna area both declined, by 74% (2.8 million ha) and 10% (2.9 million ha), respectively, between 1908 and 2000. This vegetation was replaced by a fivefold increase in cropland, from 1.2 million ha to 6.7 million ha. This LULCC implies a committed release of 0.9 Pg C (95% CI : 0.4–1.5) across the watershed for the same period, equivalent to 0.3 Mg C ha −1 yr −1 . This is at least threefold higher than previous estimates from global models for the same study area. We then used the LULCC data from before and after protected area creation, as well as from areas where no protection was established, to analyse the effectiveness of legal protection on land cover change despite the underlying spatial variation in protected areas. We found that, between 1949 and 2000, forest expanded within legally protected areas, resulting in carbon uptake of 4.8 (3.8–5.7) Mg C ha −1 , compared to a committed loss of 11.9 (7.2–16.6) Mg C ha −1 within areas lacking such protection. Furthermore, for nine protected areas where LULCC data are available prior to and following establishment, we show that protection reduces deforestation rates by 150% relative to unprotected portions of the watershed. Our results highlight that considerable LULCC occurred prior to the satellite era, thus other data sources are required to better understand long‐term land cover trends in the tropics.

Tracing long‐term tropical montane ecosystem change in the Eastern Arc Mountains of Tanzania - JEMMA FINCH; MATTHEW WOOLLER; ROB MARCHANT (Journal of Quaternary Science, 2014)
Pollen, charcoal, stable carbon and nitrogen isotope, and radiocarbon analyses are used to reconstruct a palaeoenvironmental record from the Eastern Arc Mountains (EAM), Tanzania, dating back >45 000 years. A sedimentary hiatus covering the last glacial‐interglacial transition (LGIT) and early to mid Holocene follows the lead up to the Last Glacial Maximum (LGM) period. A late Holocene portion of the record is included as a modern analogue. Before 45 000 cal a BP, very low regional pollen counts imply open vegetation surrounding the site. Subsequently, the development of extensive montane forest characterizes a relatively mesic pre‐LGM. The transition into the LGM witnessed a marked shift from C 3 ‐ to C 4 ‐dominated biomass, representing an expansion of open forest dominated by grasses. These changes may be attributed to a combination of enhanced moisture stress and CO 2 limitation, factors that may have been exacerbated by an intensive fire regime, as evident from the charcoal record. This is supported by a decrease in montane forest taxa, coupled with an associated expansion of C 4 graminoids and ericaceous heathland to form a montane grassland mosaic similar to that previously recorded on other East African mountains around the time of the LGM but not, to date, having been shown in the Eastern Arc Mountains.

Holocene mangrove dynamics and environmental change in the Rufiji Delta, Tanzania - Paramita Punwong; Rob Marchant; Katherine Selby (Vegetation History and Archaeobotany, 2013)

Terrestrial ecosystems from space: a review of earth observation products for macroecology applications - Marion Pfeifer; Mathias Disney; Tristan Quaife; Rob Marchant (Global Ecology and Biogeography, 2012)
Aim Earth observation (EO) products are a valuable alternative to spectral vegetation indices. We discuss the availability of EO products for analysing patterns in macroecology, particularly related to vegetation, on a range of spatial and temporal scales. Location Global. Methods We discuss four groups of EO products: land cover/cover change, vegetation structure and ecosystem productivity, fire detection, and digital elevation models. We address important practical issues arising from their use, such as assumptions underlying product generation, product accuracy and product transferability between spatial scales. We investigate the potential of EO products for analysing terrestrial ecosystems. Results Land cover, productivity and fire products are generated from long‐term data using standardized algorithms to improve reliability in detecting change of land surfaces. Their global coverage renders them useful for macroecology. Their spatial resolution (e.g. GLOBCOVER vegetation, 300 m; MODIS vegetation and fire, ≥ 500 m; ASTER digital elevation, 30 m) can be a limiting factor. Canopy structure and productivity products are based on physical approaches and thus are independent of biome‐specific calibrations. Active fire locations are provided in near‐real time, while burnt area products show actual area burnt by fire. EO products can be assimilated into ecosystem models, and their validation information can be employed to calculate uncertainties during subsequent modelling. Main conclusions Owing to their global coverage and long‐term continuity, EO end products can significantly advance the field of macroecology. EO products allow analyses of spatial biodiversity, seasonal dynamics of biomass and productivity, and consequences of disturbances on regional to global scales. Remaining drawbacks include inter‐operability between products from different sensors and accuracy issues due to differences between assumptions and models underlying the generation of different EO products. Our review explains the nature of EO products and how they relate to particular ecological variables across scales to encourage their wider use in ecological applications.

A palaeoecological investigation into the role of fire and human activity in the development of montane grasslands in East Africa - Jemma Finch; Rob Marchant (Vegetation History and Archaeobotany, 2011)